POTENSI GEMPA BUMI DAERAH LEBONG, PROVINSI BENGKULU - Supartoyo; Nia Kurnia Praja; Noviardi Titis Praponco; Suryo Hespiantoro (PPSDM Geominerba, 2018)
Lebong is an area in Indonesia that is prone to the earthquake caused by the subduction zone in the sea and active fault on the land. The morphotectonic analysis and the source of the destructive earthquake show that the earthquake in Lebong area is caused by the active faults of Ketaun segment, Sumatra fault, and Pelabai fault. Ketaun segment of Sumatra fault caused a destructive earthquake in 1952, while Pelabai fault caused a destructive earthquake in 2017. The destructive earthquake on Desember 6, 2017 gave us a lesson on the importance of themitigation effort in Lebong area. The mitigation effort can minimize the impact of the earthquakes that may be repeated in the future.